Pengaruh Pemberian Kompos Limbah Pertanian Terhadap Pertumbuhan dan Serapan Nitrogen Tanaman Jagung (Zea mays L.) - Roudhotul Chasanah; Anis Sholihah; Agus Sugianto (Folium : Jurnal Ilmu Pertanian, 2020)
Corn is one of the most cultivated cereals that plays an important role in meeting food needs so that the production of corn plants is increasing every year. To increase the production of corn, farmers usually use inorganic fertilizer, but in the long run, the use of inorganic fertilizer is not effective, especially in soil fertility. This study aims to determine the effect of different compost and dosages on growth and N uptake of corn plants and to obtain the optimum dosage of each compost to increase N uptake of corn plants. This research was placed in a plastic house in Losari village, Singosari, Malang with a factorial RAK experimental design with Control, where there were two factors, each factor there were four levels, namely the first factor: P1 = straw compost, P2 = soybean compost, P3 = bean compost soil, and P4 = sugarcane compost, whereas the second factor is D1 = 5 tons / ha, D2 = 10 tons / ha, D3 = 15 tons/ha, and D1 = 20 tons / ha. There are 16 combinations plus control = 17 treatments, 17x 3 replications x 3 samples = 153 experimental units. Data analysis used 5% Anova if it was tested further using a 5% BNJ and to determine the optimum dose regression analysis was performed. The results showed that separately the P3 treatment gave the best results on parameters of plant height, stem diameter, number of leaves, and leaf area. P3 treatment gives the best optimum dosage results on N-total uptake with a determination value of 94.46%; the optimum dose obtained is 11.44 tons/ha.